The relationship between gender policies and the creation of businesses by women - Teixeira, Daiane Martins; Borges Júnior, Cândido Vieira; Almeida, Marcos Inácio Severo de (REGEPE Entrepreneurship and Small Business Journal, 2023)
Objective: to analyze the effects of gender policies on women’s business creation. Methodology/approach: quantitative approach, with secondary data extracted from the Municipal Basic Information Survey (MUNIC); and public CNPJ data from the Federal Revenue Service. The level of analysis was restricted to the 246 municipalities in the state of Goiás. From this, tests were performed with two negative binomial regression models. Main results: for women entrepreneurs who created their businesses alone, gender policies showed a positive relationship; on the other hand, for those who created companies in partnership, no influence was identified. With these results, it is possible to understand that the same support measures may not have similar effects to all types of business creation by women. Theoretical-methodological contributions: this study showed that, when analyzing public policies as a means of promoting entrepreneurship by women, one should consider the existing differences between them, either in the contextual aspects in which they are inserted, or as the specificity of each group, bearing in mind that needs different require different support actions. Relevance/originality: especially for women who are self-employed, according to this research, the existence of gender policies proves to be an important factor, since difficulties, such as those generated by discrimination, can be faced, thus meeting the needs of access to education, equality, health and safety.